Transition‐Metal‐Catalyzed Carbohalogenative 1, 2‐Difunctionalization of C−C Multiple Bonds. Issue 19 (26th August 2020) - Bag, Debojyoti; Mahajan, Shivangani; Sawant, Sanghapal D.
Abstract: Transition‐metal‐catalyzed 1, 2‐carbohalo‐functionalization reactions of C−C multiple bonds have emerged rapidly over the past decade as a powerful tool for generating a new carbon‐carbon and carbon‐halogen bond via transposition of an existing carbon‐halogen σ bond. Exploring this highly efficient mode of carbon‐carbon multiple bond difunctionalization, various research groups have established novel strategies for the synthesis of organohalides by utilizing wide variety of transition metal catalysts under mild reaction conditions, avoiding stoichiometric waste of by‐products, and with improved levels of chemo‐, regio‐, and stereoselectivities. Most of the 1, 2‐carbohalo‐functionalization reactions involve either the carbon‐halogen reductive elimination mechanism or the atom transfer radical addition (ATRA) mechanism. This review summarizes the recent progress in the area of transition‐metal‐catalyzed intra‐ and intermolecular 1, 2‐carbohalo‐functionalization reactions of carbon‐carbon multiple bonds and explicates the underlying potentiality and challenges within the field. Abstract :